A narrativa cinematográfica alegórica/simbólica no cinema de animação - Luciana Fagundes Braga Ferreira (2005)
The allegoric/symbolic narrative considered as category of understanding, in this dissertation, had the objective of organizing and comparing, in general, a traditional and renovational context in animation cinema. For such endeavor, theoretical concepts of symbolic mode and allegoric mode, coined by the semioticist Umberto Eco, were used. It was, then, possible to reconstruct in the history of animation the lourishment of an allegoric/symbolic narrative tendency that gained great expressivity in the decades of 1950 and 1960, and that remains present, still today, in films produced principally in Eastern Europe. The analysis proposed verified that the economic, cultural and political changes that occurred in the western world, following the post-war period, enabled the creation of an expressive number of allegoric/symbolic films and the formation of spectators opened to receptivity of this significant form of narrative.